Blast-furnace slag - Yüksel, İsa (Elsevier, 2018)
The use of industrial by-products such as blast furnace slag (BFS) partially instead of natural resources in cement and concrete industry is beneficial and necessary from the viewpoint of sustainable development. Ground BFS is used in cement and concrete in different forms for many years in all over the world. This chapter presents information about storage and handling, classification, and different utilization forms of BFS in concrete and cement industry. Moreover, fresh and hardened properties and durability characteristics of cements, mortars, or concretes incorporating BFS is considered. It is concluded with considering current codes and standards about BFS and the new developing forms of utilization of BFS such as usage in geopolymer concrete that is an innovative and ecofriendly construction material and an alternative to Portland cement concrete, use as fine aggregate without grounding in concrete or combined usage with other industrial wastes with or without grounding. © 2018 Elsevier Ltd. All rights reserved.
Keywords: Blast furnace slag; Concrete; Durability; Granulation; Replacement